2014
DOI: 10.14314/polimery.2014.459
|View full text |Cite
|
Sign up to set email alerts
|

Photopolymerization kinetics and molecular interactions in methacrylate-imidazolium based ionic liquid systems

Abstract: Photopolymerization of poly(ethylene glycol) monomethacrylate (PEGMM) in two imidazolium based ionic liquids (ILs) differing with the anion size and H-bond accepting ability, i.e. 1-ethyl-3-methylimidazolium tetrafluoroborate ([EMIm][BF 4 ]) and 1-ethyl-3-methylimidazolium trifluoroacetate ([EMIm][ATF]) was investigated to find the effect of the IL anion on propagation k p and termination rate k t b coefficients (by DSC) as well as molecular interactions in the system (on the basis of viscosity and FT-IR measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…As mentioned previously, studies examining the role of ILs as solvents in radical polymerization have shown that ILs are unique, increasing the rate of propagation while decreasing the rate of termination. [39][40][41]72,73 Multiple explanations for this behavior have been proposed, including polarity-associated decreases in the activation energy of polymerization as well as effects resulting from both the inherent viscosity of the solvent as well as specific interactions between the IL media and the monomers. 40,41,72,73 However, several alternative hypotheses have been proposed attributing the improved reaction kinetics of vinyl monomers to the formation of polar and nonpolar domains within the IL solvent.…”
Section: -68mentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned previously, studies examining the role of ILs as solvents in radical polymerization have shown that ILs are unique, increasing the rate of propagation while decreasing the rate of termination. [39][40][41]72,73 Multiple explanations for this behavior have been proposed, including polarity-associated decreases in the activation energy of polymerization as well as effects resulting from both the inherent viscosity of the solvent as well as specific interactions between the IL media and the monomers. 40,41,72,73 However, several alternative hypotheses have been proposed attributing the improved reaction kinetics of vinyl monomers to the formation of polar and nonpolar domains within the IL solvent.…”
Section: -68mentioning
confidence: 99%
“…[39][40][41]72,73 Multiple explanations for this behavior have been proposed, including polarity-associated decreases in the activation energy of polymerization as well as effects resulting from both the inherent viscosity of the solvent as well as specific interactions between the IL media and the monomers. 40,41,72,73 However, several alternative hypotheses have been proposed attributing the improved reaction kinetics of vinyl monomers to the formation of polar and nonpolar domains within the IL solvent. 42,43,74 Thurecht et al examined the mechanism of radical polymerization of MMA in common IL solvents by determining the effect of several kinetic parameters on the rate of polymerization and polymer molecular weights.…”
Section: -68mentioning
confidence: 99%
“…Interest in the use of these low‐melting ( T m < 100 °C), primarily organic salts stems from their unique properties such as a negligible vapor pressure and a high degree of thermal stability that have lead them to be proposed as alternatives to conventional solvents in a variety of processes . Thermally initiated radical polymerizations of methyl methacrylate (MMA) were some of the first polymerization reactions studied in IL solvents (e.g., 1‐butyl‐3‐methylimidazolium hexafluorophosphate ([C 4 mim][PF 6 ]), and the kinetics of these processes have been extensively investigated for a variety of other monomers and methods of polymerization . Analysis of the rate of propagation ( R p ) using pulsed laser polymerization (PLP) and size exclusion chromatography (SEC) has generally indicated that IL solvation increases propagation rate constants ( k p ) .…”
Section: Introductionmentioning
confidence: 99%
“…The addition of lithium bistriflimide RTIL to 1-vinylimidazole was used to significantly improve monomer conversion and photopolymerization rate, possibly as a result of coordination between the imidazole and the Li + cation (54). Photopolymerization of poly (ethylene glycol) (PEG)-monomethacrylate was studied in [BMIM]BF 4 and 1-ethyl-3-methylimidazolium trifluoroacetate to determine the effect of RTIL on both propagation and termination rates (55).…”
Section: Free Radical Polymerizationmentioning
confidence: 99%